Antisperm antibodies as a factor of male infertility. Relevance, modern methods of diagnosis and treatment - O. A. Nikiforov; N. V. Avramenko; V. V. Mikhailov (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2017)
According to WHO statistics 40 % of childless marriage is due to factors of male infertility. One of them is the presence of antisperm antibodies in the male organism, which may be in blood serum, on the surface of spermatozoids and seminal plasma.